2009
DOI: 10.1177/1538574409352691
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Fracture of Polytetrafluoroethylene Axillofemoral Bypass Graft

Abstract: We report traumatic disruption of a ringed polytetrafluorethylene (PTFE) axillofemoral bypass (AFB) graft due to a fall. We also review the literature of previously reported blunt traumatic PTFE graft disruptions. A 75-year-old man with previous bilateral AFB grafting presented with a painful left chest wall mass after a fall from standing height. Chest computed tomography (CT) revealed a large chest wall hematoma. The patient underwent evacuation of the hematoma, resection of the fractured graft, and placemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…A flexible plastic tube is placed to divert blood from the axillary artery directly to the femoral arteries, bypassing the areas of blockage. This procedure is indicated for patients with peripheral vascular disease, aortoiliac occlusive disease, or infectious artery disease [ 11 , 12 ]. In a comparative study, Passman et al examined the morbidity, mortality, and patency rates for aortofemoral bypass grafting and BiFAXB grafting.…”
Section: Discussionmentioning
confidence: 99%
“…A flexible plastic tube is placed to divert blood from the axillary artery directly to the femoral arteries, bypassing the areas of blockage. This procedure is indicated for patients with peripheral vascular disease, aortoiliac occlusive disease, or infectious artery disease [ 11 , 12 ]. In a comparative study, Passman et al examined the morbidity, mortality, and patency rates for aortofemoral bypass grafting and BiFAXB grafting.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of graft ruptures is around 5% [11]. There are limited number of studies reporting axillo-femoral graft ruptures and distortions [9][10][11][12][13][14][15]. PTFE graft rupture and development of pseudoaneurysm are rare complications in vascular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from several case reports of disrupted bypasses without proven trauma history, 3 authors reported pseudoaneurysms in nonanastomotic regions of an axillofemoral graft because of preceding trauma [2] , [3] . The patients were treated either with an interposition graft.…”
Section: Discussionmentioning
confidence: 99%
“…We are presenting a patient sustaining a complete rupture of a polytetrafluoroethylene (PTFE) axilloprofundal bypass in his thoracic midportion after proven blunt trauma. Until now, only 3 authors have reported similar cases [2] , [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%